Perspectives of gene therapy in stem cell tissue engineering - Gößler, Ulrich; Riedel, Katrin; Hörmann, Karl; Riedel, Frank (Cells tissues organs, 2006)
Tissue engineering is an interdisciplinary field that applies the principles of engineering and life sciences toward the development of biological substitutes that restore, maintain or improve tissue function. It is hoped that forming tissue de novo will overcome many problems in plastic surgery associated with such areas as wound healing and the immunogenicity of transplanted tissue that lead to dysfunctional repair. Gene therapy is the science of the transfer of genetic material into individuals for therapeutic purposes by altering cellular function or structure at the molecular level. Recently, tissue engineering has been used in conjunction with gene therapy as a hybrid approach. This combination of stem-cell-based tissue engineering with gene therapy has the potential to provide regenerative tissue cells within an environment of optimal regulatory protein expression and would have many benefits in various areas such as the transplantation of skin, cartilage or bone. The aim of this review is to outline tissue engineering and possible applications of gene therapy in the field of biomedical engineering as well as basic principles of gene therapy, vectors and gene delivery.